(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Ana-Maria Bănică explores affect theory and mimetic communication by analyzing Spike Jonze’s film Her and Olga Tokarczuk’s short story „Visit”. The study investigates how digital spaces redefine human subjectivity, transforming mimesis into a synesthetic form of knowledge. The author highlights the role of shame as a creative engine born from the mind-body conflict. Ultimately, artistic acts are presented as bridges between the organic and inorganic, adapting human identity to a complex post-human reality. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.